Evaluation of the application of gamification in the discipline of Software Engineering in times of pandemic - Castro, Vitor; Santos, Adam (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
The new coronavirus pandemic promoted structural changes in society due to the need to elevate social isolation to the extreme. In this context, the majority of educational institutions have chosen to continue their activities remotely. One of the strategies used to engage students with academic activities is the use of gamification. Due to the new scenario, driven by the pandemic, this study aims to present and evaluate the application of gamification by comparing its use in the remote and in-person contexts, as well as the necessary adaptations for the new scenario. The comparison took place between two Software Engineering classes, one being in-person and the other in remote format. As initial results, a positive evaluation related to the application of the game was achieved, greater than 80% for the two teaching formats.